Mental Loneliness is a Massive Problem for People - Alarcon, Julián Andres (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Mental health in our current society is a problem of loneliness. In our times, when you do nothave emotional support, you can fall into a mental crisis. We could solve this situation. However, yourthoughts and emotions will be working simultaneously. We have to overcome these state of affairs,alone or accompanied.